Structured catalysts for partial oxidations - Campos, Victor J. M. de (2001)
The objective of the present work is centred on the analysis of the behaviour of fixed-bed reactors packed with structured catalysts when a partial oxidation takes place. The fluid flow within an element, formed by the intersection of two adjacent corrugated plates, was mathematically modelled and numerical simulations were performed in order to study possible optimising of the catalyst structure. A simple model, involving the continuous stirred tank approach, was used to simulate the performance of the catalyst in an industrial reactor. The profiles of temperature, concentration, velocity and pressure along the reactor were obtained through the global mass balance, partial molar balances, conservation of moment, energy balance and mechanical energy balance. These equations were applied to an exothermic reactional system, the selective oxidation of methanol to formaldehyde, in order to evaluate the possibility of application of these catalysts in industry. Various parameters specific to the catalyst and the reactional system were tested in order to achieve a better understanding of the behaviour of these structured packing. The comparison with the heterogeneous model predictions for a random packing and with industrial values pointed out that the choice of parameters is fundamental to the performance of the catalyst. The adjustments to the parameters allows for significant improvements in some of the more troublesome aspects of the reactional system. Lowering the hot-spot, reducing the progress of the secondary reaction and reducing the pressure drop are the main enhancements that these structured catalysts can offer.